2015
DOI: 10.1103/physrevb.92.100303
|View full text |Cite
|
Sign up to set email alerts
|

From soft harmonic phonons to fast relaxational dynamics inCH3NH3PbBr3

Abstract: The lead-halide perovskites, including CH3NH3PbBr3, are components in cost effective, highly efficient photovoltaics, where the interactions of the molecular cations with the inorganic framework are suggested to influence the electronic and ferroelectric properties. CH3NH3PbBr3 undergoes a series of structural transitions associated with orientational order of the CH3NH3 (MA) molecular cation and tilting of the PbBr3 host framework. We apply high-resolution neutron scattering to study the soft harmonic phonons… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

18
91
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(111 citation statements)
references
References 40 publications
18
91
2
Order By: Relevance
“…The X-ray diffraction spots at 160 K shown in figure 3a are labeled for the conventional settings of the tetragonal I4/mcm structure (one antiphase octahedral tilt [23]). On the other hand, results obtained at 140 K shown in Fig 3c indicate that the ordered low temperature phase exhibits an orthorhombic Pnma symmetry, in agreement with a previous result by neutron powder diffraction by Swainson et al [24] The X-ray diffraction map at 150 K shown in figure 3b exhibits additional satellite reflections at a fixed wave vectors q away from each main reflection. Interestingly, these new satellites cannot be described by rational numbers of the reciprocal unit cell vectors.…”
supporting
confidence: 80%
See 2 more Smart Citations
“…The X-ray diffraction spots at 160 K shown in figure 3a are labeled for the conventional settings of the tetragonal I4/mcm structure (one antiphase octahedral tilt [23]). On the other hand, results obtained at 140 K shown in Fig 3c indicate that the ordered low temperature phase exhibits an orthorhombic Pnma symmetry, in agreement with a previous result by neutron powder diffraction by Swainson et al [24] The X-ray diffraction map at 150 K shown in figure 3b exhibits additional satellite reflections at a fixed wave vectors q away from each main reflection. Interestingly, these new satellites cannot be described by rational numbers of the reciprocal unit cell vectors.…”
supporting
confidence: 80%
“…This rapid softening behavior is drastically different compared to the peaks observed in the orthorhomic phase. Interestingly, both the frequency and its strong temperature dependence of this mode match very well with the quickly softening mode observed within the low temperature orthorhombic phase using inelastic neutron scattering [24], shown in Figure 4c. In the orthorhombic phase, this softening mode was associated purely with the tilting of the PbBr 3 octahedral framework, likely away from Brillouin zone center.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…Since ARPES is a surface-sensitive technique, the reduced symmetry at the surface may enhance non-centrosymmetric fields and the measured Rashba splitting. In the bulk, CH 3 NH 3 PbBr 3 forms an ordered orthorhombic structure of P nma symmetry at low temperature [41,42], and a disordered cubic structure with an average P m3m symmetry at room temperature [29,36,43]. Both structures are centrosymmetric after averaging over a length scale probed by x-ray and neutron diffraction, with no Rashba-type spin-splitting expected.…”
mentioning
confidence: 93%
“…It collects two-dimensional angular photoelectron distribution patterns from an acceptance cone covering −35 • to 45 • both along and perpendicular to the plane of light incidence without the need to move sample or analyzer. During cooling, we perform in situ using photoluminescence spectroscopy reproducing the phase transitions reported in literature [29], see figure S2 (b) [27].…”
mentioning
confidence: 99%